2015
DOI: 10.1007/s11707-015-0518-3
|View full text |Cite
|
Sign up to set email alerts
|

Mapping paddy rice distribution using multi-temporal Landsat imagery in the Sanjiang Plain, northeast China

Abstract: Information of paddy rice distribution is essential for food production and methane emission calculation. Phenology-based algorithms have been utilized in the mapping of paddy rice fields by identifying the unique flooding and seedling transplanting phases using multi-temporal moderate resolution (500 m to 1 km) images. In this study, we developed simple algorithms to identify paddy rice at a fine resolution at the regional scale using multi-temporal Landsat imagery. Sixteen Landsat images from 2010–2012 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 42 publications
1
25
0
3
Order By: Relevance
“…Our maps are able to show detailed shifts in rice area on the local to county scale, which could not be deduced from the publicly-available agricultural statistics. The biggest observable change during the time period studied is the large increase in rice area in Heilongjiang, which has also been reported by previous studies [36,38,40,42]. From 2005 onward, paddy rice area in Heilongjiang increased at an unprecedented rate.…”
Section: Discussionsupporting
confidence: 82%
“…Our maps are able to show detailed shifts in rice area on the local to county scale, which could not be deduced from the publicly-available agricultural statistics. The biggest observable change during the time period studied is the large increase in rice area in Heilongjiang, which has also been reported by previous studies [36,38,40,42]. From 2005 onward, paddy rice area in Heilongjiang increased at an unprecedented rate.…”
Section: Discussionsupporting
confidence: 82%
“…With rapid socio-economic development in this area, more land is required for housing, infrastructure and industry, and rice cultivation is increasingly becoming prominent in northeast China [33]. Even though rice fields have been shifted to the peri-urban, apart from competition from residential and industrial land-uses, they are also seriously contested by such lucrative farming activities as aquaculture, horticulture, and other high income earning and shorter duration crops.…”
Section: Study Areamentioning
confidence: 99%
“…Previous studies has used the thematic map of wetland to deal with this problem and suggested the need to develop a MODIS- or Landsat-based natural wetland mask (Jin et al, 2015; Zhang et al, 2015). A more detailed analysis of the dynamics of paddy rice and natural wetland might give us more clues to solve this problem.…”
Section: Introductionmentioning
confidence: 99%